Pengaruh Pengetahuan Kewirausahaan, Karakter Wirausaha dan Motivasi Terhadap Keputusan Berwirausaha Siswa - Nanda Sari; Fajar Pasaribu; Dewi Andriyani (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to investigate the effect of determinated: 1). The effects of entrepreneurship knowledge to the decision of entrepreneurship of students; 2) The effects of character entrepreneur to the decision of entrepreneurship of students; 3) The effects of motivation to the decision of entrepreneurship of students; 4) the effects of interaction of entrepreneurship knowledge, character entrepreneur and motivation to the decision of entrepreneurship of students. This is Quantitative description study. Study population were students of SMK Muhammadiyah Tanjung Anom. The study sample as are 80 students take from slovin formula with taken proporsional sampling. The data analisys technique was perfomed by multiple linier progressions. The result study of this are as follows; 1) the entrepreneurship knowledge has a direct positive influence on the decision of entrepreneurship with significant value of 0,00; 2) character entrepreneur has a direct positive influence on the decision of entrepreneurship with significant value 0,005; 3) motivation has a direct positive influence on the decision of entrepreneurship with significant value 0,00; 4) conclude 30,2% of students in decision of entrepreneurship can be influenced the entrepreneurship knowledge, character entrepreneur and motivation. Furthermore, the remaining 69,8% is influenced by other factors, namely evironment factors and contextual factors.